Antiproliferative xylan from corn cobs induces apoptosis in tumor cells. (15th April 2019) - Melo-Silveira, Raniere Fagundes; Viana, Rony Lucas Silva; Sabry, Diego Araujo; da Silva, Rodrigo Augusto; Machado, Daisy; Nascimento, Ana Karina Lima; Scortecci, Katia Castanho; Ferreira-Halder, Carmen Veríssima; Sassaki, Guilherme Lanzi; Rocha, Hugo Alexandre Oliveira
Highlights: Xylan from corn cobs exhibits antiproliferative activity against tumor cells. Xylan increases the ratio of Bax:Bcl-2. Xylan increases the amount of cytochrome c, caspase 3, and AIF. Xylan induces caspase-dependent and -independent apoptosis in HeLa cells. Abstract: Xylan is one of the most abundant hemicellulose constituents in the plant kingdom. We extracted xylan from corn cobs (XCC) using ultrasound. The structure of XCC was determined by NMR analysis, which revealed a composition of xylose:glucose:arabinose:galactose:mannose:glucuronic acid in a molar percentage ratio of 48:21:16:10:2.5:2.5. XCC induced the proliferation of murine macrophage cells (RAW 264.7) and inhibited the proliferation of human lung adenocarcinoma epithelial cells (A549) by 20% and human cervical adenocarcinoma cells (HeLa) by 60%. Several cell death-associated morphological changes were observed after the exposure of HeLa cells to XCC for 24 h. In addition, by using fluorescent probes, we observed a larger number of irregular and pyknotic nuclei with condensed chromatin bodies (nuclear condensation). FACS analysis showed an increase in the number of annexin V-positive and propidium iodide (PI)-positive cells (37.0%) in the presence of XCC compared with that of the negative control cells (5.0%). XCC also increased the ratio of Bax:Bcl-2 (3.5:1) and the levels of cytochrome c, caspase 3, and apoptosis-inducing factor (AIF) in treated cells. Therefore, the results demonstrated the antiproliferative potential of XCC, which induced apoptosis in HeLa cells.